A multiscale investigation of uranium(VI) interaction with a freshwater diatom species - Yihua He; Vladyslav Sushko; René Hübner; Harald Foerstendorf; Robin Steudtner; Johannes Raff; Clarisse Mallet; Anne-Hélène Le Jeune; Aude Beauger; Vincent Breton; Olivier Péron; Thorsten Stumpf; et al. (Scientific Reports)
Abstract Diatoms are essential bio-indicators for assessing the impact of heavy metals and hazardous materials on aquatic ecosystems. This study seeks to advance our understanding of the interaction between uranium (U) and the freshwater diatom species Achnanthidium saprophilum, employing macroscopic, microscopic, and spectroscopic approaches. Bio-association experiments with hexavalent U (U(VI)) were conducted during various diatom growth phases and revealed time- and concentration-dependent U retention by the diatoms. U bio-association was observed by scanning electron microscopy and energy-dispersive X-ray spectroscopy (EDX), indicating co-localization of U with phosphorus (P). Time-resolved laser-induced fluorescence spectroscopy on U(VI)-associated diatoms suggested the formation of two adsorbed U(VI) species, whose proportions depend on the diatom growth phase. Fourier-transform infrared spectroscopy confirmed the interaction of U(VI) dominated by carboxyl groups on diatoms, while the contribution of silanol groups from the diatom frustule appeared insignificant. U bio-association experiments revealed also U incorporation into diatom cells, confirmed by transmission electron microscopy coupled with EDX. Co-localization of U with P within the vacuole was evident, suggesting co-precipitation of various metals, including U, in form of phosphates. The results of this study highlight not only the adsorption but also the internalization of U by diatoms, which influences the fate of U in aquatic ecosystems and affects its mobility and bioavailability. These findings are highly relevant for the further development of radioecological models.